Gibson-Getty-McClure families papers - Getty, George W.; McClure, Charles, 1838-1902.
Correspondence, diaries, financial papers, military papers, and other material relating to various members of these allied families from Cumberland County, Pa. Gibson family papers pertain chiefly to the Revolutionary War service of George Gibson (1747-1791). Papers of George W. Getty document his Civil War service with the Army of the Potomac in Virginia, various Indian campaigns, and the Fitz-John Porter court-martial. Papers of Charles McClure (1838-1902) relate chiefly to his military service with the U.S. Army at posts in the U.S. including Santa Fe, N.M., and in the Philippine Islands during the Spanish-American War.
Family correspondents include Annie Barbara Gibson, Fannie M. Gibson, George Gibson, (1783-1861), George Gibson (1826-1888), John Bannister Gibson, Charles McClure, Jr., George McClure, Margaretta Gibson McClure, and William McClure. Other correspondents include John Rutter Brooke, Ambrose Everett Burnside, Amos Beebe Eaton, Ulysses S. Grant, Francis B. Jones, Roswell Hawks Lamson, John Pope, William Beatty Rochester, William S. Rosecrans, John McAllister Schofield, Philip Henry Sheridan, William T. Sherman, and Hazard Stevens.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Library of Congress Serial and Government Publications Division.
Library of Congress Music Division.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brooke, John Rutter, -- 1838-1926 -- Correspondence; Burnside, Ambrose Everett, -- 1824-1881 -- Correspondence; Eaton, Amos Beebe, -- 1806-1877 -- Correspondence; Gibson, Annie Barbara, -- 1817-1857 -- Correspondence; Gibson, Fannie M. -- Correspondence; Gibson, George, -- 1747-1791.; Gibson, George, -- 1783-1861 -- Correspondence; Gibson, George, -- 1826-1888 -- Correspondence; Gibson, John Bannister, -- 1780-1853 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Jones, Francis B. -- Correspondence; Lamson, Roswell Hawks -- Correspondence; McClure, Charles, -- 1875-1901 -- Correspondence; McClure, George -- Correspondence; McClure, Margaretta Gibson, -- 1814- -- Correspondence; McClure, William -- Correspondence; Pope, John, -- 1822-1892 -- Correspondence; Porter, Fitz-John, -- 1822-1901.; Rochester, William Beatty, -- 1826-1909 -- Correspondence; Rosecrans, William S. -- 1819-1898 -- Correspondence; Schofield, John McAllister, -- 1831-1906 -- Correspondence; Sheridan, Philip Henry, -- 1831-1888 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Stevens, Hazard, -- 1842-1918 -- Correspondence; Getty family; Getty family -- Correspondence; Gibson family; Gibson family -- Correspondence; McClure family; McClure family -- Correspondence; United States. -- Army; United States. -- Army of the Potomac; Courts-martial and courts of inquiry; Fortification -- New Mexico -- Santa Fe; Fortification -- United States; Indians of North America -- Wars; Military bases -- New Mexico -- Santa Fe; Military bases -- United States; Spanish-American War, 1898 -- Philippines; Cumberland County (Pa.) -- History; Cumberland County (Pa.) -- Social life and customs; Pennsylvania -- Social life and customs; United States -- History -- Revolution, 1775-1783.; Virginia -- History -- Civil War, 1861-1865.